Model Penjadwalan Pembagian Air pada Sistem Irigasi (Studi Kasus: Irigasi Riam Kanan) - Fachrurazie, Chairil (Department of Civil Engineering, Diponegoro University, 2005)
The main problem of the agricultural activity is unbalanced system on the water supply to the rice plant field. This problem is faced on the case study of the B.Gt.6 Sub Area B Riam Kanan Irrigation System, which is unmatched between the water supply scheduling and its implementation on the field. To solve this problem is, determining the mathematical model which is easily to calculate. The aim of the mathematical model is to obtain the water supply schedule on the irrigation system from the channel to the rice plant field. The model of the linear program is obtained, which is hoped to be implemented on the irrigation network system actually with the qualitative aspect of the result by the case study in the B.Gt.6. Implementation of this study case obtaining the water supply schedule of the irrigation water areÂ xi3=36 and yi3=110Â for the destination function-1 and also xi3=36 and yi3=113Â for the destination function-2. The value of the minimum loss (z) is 6328 per square area unit in one day for the model I and 0 (zero) per square area unit in one day for the model II.Keywords: Water supply scheduling, linear program modelPermalink: http://www.ejournal.undip.ac.id/index.php/mkts/article/view/3895[How to cite: Fachrurazie, C., 2005, Model Penjadwalan Pembagian Air pada Sistem Irigasi (Studi Kasus: Irigasi Riam Kanan), Jurnal Media Komunikasi Teknik Sipil, Volume 13, Nomor 1, pp. 39-47] The main problem of the agricultural activity is unbalanced system on the water supply to the rice plant field. This problem is faced on the case study of the B.Gt.6 Sub Area B Riam Kanan Irrigation System, which is unmatched between the water supply scheduling and its implementation on the field. To solve this problem is, determining the mathematical model which is easily to calculate. The aim of the mathematical model is to obtain the water supply schedule on the irrigation system from the channel to the rice plant field. The model of the linear program is obtained, which is hoped to be implemented on the irrigation network system actually with the qualitative aspect of the result by the case study in the B.Gt.6. Implementation of this study case obtaining the water supply schedule of the irrigation water are xi3=36 and yi3=110 for the destination function-1 and also xi3=36 and yi3=113 for the destination function-2. The value of the minimum loss (z) is 6328 per square area unit in one day for the model I and 0 (zero) per square area unit in one day for the model II. Keywords: Water supply scheduling, linear program model